A simulation system for WMN based on SA: performance evaluation for different instances and starting temperature values. (1st December 2014) - Sakamoto, Shinji; Kulla, Elis; Oda, Tetsuya; Ikeda, Makoto; Barolli, Leonard; Xhafa, Fatos
With the emergence of wireless networking paradigm, several optimisation problems are showing their usefulness to the efficient design of such networks. These problems are related, among others, to optimising network connectivity, coverage and stability. The resolution of these problems turns out to be crucial for optimised network performance. In the case of wireless mesh networks (WMN), such problems include computing placement of nodes (mesh router nodes, gateways and distribution of mesh client notes), so that network performance is optimised. Previously, we have proposed and implemented a simulation system, which uses simulated annealing (SA) algorithm, to optimise network performance by computing mesh routers' positions in wireless mesh networks (WMNs). We consider different temperature values and different instances in our simulations. In this work, we use the WMN-SA system to find the optimal distribution of router nodes in order to provide the best network connectivity and the best coverage for distributed mesh clients. From simulation results, we found that when the size of the instance increases, the size of GC and NCMC decrease. Moreover, the larger instances are affected more by higher temperatures.